Long-read sequencing reveals chromothripsis in a molecularly unsolved case of Cornelia de Lange syndrome - Bestetti, Ilaria; Crippa, Milena; Sironi, Alessandra; Bellini, Matteo; Tumiatti, Francesca; Ballabio, Sara; Ceriotti, Ferruccio; Memo, Luigi; Iascone, Maria; Larizza, Lidia; Finelli, Palma (Frontiers in Genetics, 2024)
Thanks to a Long Read Sequencing approach here we report a molecularly solved case of a proband with a clinical diagnosis of Cornelia de Lange Syndrome (CDLS), a multisystemic disorder whose causative molecular defects involve the cohesin complex genes, with NIPBL located at 5p13.2 accounting for about 50 to 60% of CDLS cases. The first tier tests revealed an abnormal karyotype 46,XY,t(5;15)(p13;q25)dn and a preserved NIPBL sequencing. Copy number variants at the translocation breakpoints, in disease genes, or in probably pathogenic loci, were excluded by a-CGH analysis. Through FISH analysis on derivative chromosome 5 the breakpoint was relocated 3Mb far from NIPBL 5'UTR, which seemed fully maintained as the FISH-probe mapping to the gene showed no split signals. Moreover tri-color FISH revealed on derivative 5 an apparently balanced paracentric inversion including NIPBL. Based on the strong clinical suspicion we evaluated NIPBL transcript by RT-qPCR that revealed a normal amount of transcript till exon 22 and a halved amount of transcript from exon 23 to 3'UTR, indicating the expression of a truncated transcript probably leading to a defective protein. Despite RT-qPCR confirmed the patient's CDLS clinical diagnosis, the molecular mechanism underlying this event remained an unsolved challenge for years. The LRS approach with Nanopore technologies was able to fill the gap in this complex scenario and highlighted a chromothripsis event marked out at 5p13.2 by 36 breaks clustered in a 7.3 Mb region. NIPBL gene was disrupted by 16 breaks and the resulting fragments relocated in different positions and orientations. Long read sequencing confirmed the previous findings and has proven to be crucial to define the complex chromosomal rearrangement in this patient which escaped current diagnostic investigations. Its application in the clinical practice will contribute to solve the unsolved.